(untitled) (Research, Society and Development, 2022)
The objective of this work was to analyze the historicity of the structure of the official expert report, of a criminal nature, showing how the power of the agents involved in the criminal prosecution were shaping the structure of this legal document. For this purpose, a comparison of the structure of the actual reports with the reports produced in the period from 1890 to 1930 was carried out. The analysis showed temporal continuities in the writing of the report at least 150 years ago. In Brazil, the structure of the forensic report was being delineated within the criminal process in view of the inquisitorial and notary logic of registration and written authentication of documents. So, the forensic report have incorporated certain organizational and hierarchical structures that were preserved and reinforced by the legal framework. These preserved structures reflect disputes of power and influence over the forensic science that has been perpetuated until the present day, establishing restrictions and discontinuities of the forensic science act.